Improving Capacity of Older Adults with Locomotive Syndrome Stage 1 Living in Nursing Home: A Pilot Clinical Trial - Michael Prayogo; Damayanti Tinduh; Dewi Poerwandari; Rwahita Satyawati Dharmanta; Sri Mardjiati Mei Wulan; Yukio Mikami; Soenarnatalina Melaniani (Annals of Geriatric Medicine and Research, 2022)
Background Aging causes locomotive syndrome (LS), which is characterized by difficulty in walking. The present study determined the effects of locomotion training and regular aerobic exercise programs on the aerobic capacity of older nursing home residents with LS stage 1. Methods This randomized controlled trial included 24 participants aged 60–80 years with LS stage 1 residing in a single nursing home in Surabaya, Indonesia. The participants were randomly assigned to either the locomotion training group (LTG) or the control group (CG). Both the groups performed 30 minutes of a daily group-based aerobic exercise program for 8 weeks. The LTG performed additional locomotion training three times weekly, with three sets per session, gradually increasing to five sets per session according to the participant’s tolerance. Two-minute walking test (2MWT) values before and after the 8-week intervention were determined in both the groups and converted to maximum oxygen consumption (VO2max) values. Results After 8 weeks of intervention, a significant increase in VO2max was observed in both the groups (both p<0.05). The LTG showed a more significant improvement in VO2max (p<0.05) compared to the CG. Conclusion The study results demonstrated the positive effect of 8 weeks of locomotion training and regular aerobic exercise programs in improving the aerobic capacity of older adult nursing home residents with LS stage 1.